Prevalence of hr‑HPV genotypes among vaccinated and unvaccinated women in central Italy: a retrospective study: hr‑HPV genotypes in women of central Italy - Serafini, Angela; De Santi, Mauro; Schiavano, Giuditta Fiorella; De Nictolis, Michele; Brandi, Giorgio (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Human papillomavirus is the most common sexually transmitted infection worldwide. Data on the prevalence of genital HPV infection are heterogeneous since the risk of infection and the gravity of diseases is depending by geography, socioeconomic conditions, assessed population. In the present study, it was evaluated the prevalence of high-risk HPV genotypes in women who have attended at a diagnostic laboratory in the Marche region (Italy) for cervical cancer test. Methods: Pap tests and biomolecular analyses were conducted in 875 women for the identification of hr-HPV genotypes and common concomitant infections of the genital tract. Multiplex Real-time PCR was used for the simultaneous identification of hr-HPV 16, 18, and non-specified pooled detection of HPV 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68. Results: Of 875 women tested, 228 (26%) resulted hr-HPV positive, with a higher prevalence (28%) in the range of 35-44 years. In the unvaccinated group,the prevalence of infection was about 5 times higher vs. vaccinated women. The hr-HPV16 was the most diagnosed genotype, followed by hr-HPV18. The high-grade cytological abnormalities were identified only in unvaccinated women. Finally, 71 % of hr-HPV infections were concomitant with other infections of the genital tract. Conclusions: A meaningful diffusion of hr-HPV, prevalently genotypes HPV-16, was observed in women > 25 years, frequently associated with other sexually transmitted infections, and a substantial difference in the risk of cervical cancer in unvaccinated compared to vaccinated women. The enhancement of primary and secondary prevention interventions must be further incentivized.